Carboxylated carbon nanotubes with high electrocatalytic activity for oxygen evolution in acidic conditions. Issue 1 (21st December 2021) - Zhang, Xin; Zhang, Wenqing; Dai, Jianying; Sun, Mingzi; Zhao, Jun; Ji, Lifei; Chen, Lin; Zeng, Fanlong; Yang, Fengchun; Huang, Bolong; Dai, Liming
Abstract: Since most electrocatalysts for oxygen evolution reaction (OER), except for precious metal oxides RuO2 and IrO2, are unstable in harsh acidic solutions, it is highly desirable to develop high‐performance OER electrocatalysts for acidic media, though it is still a big challenge. Herein, we report a simple strategy to produce carboxyl‐enriched multiwalled carbon nanotubes (COOH‐MWNTs) that exhibit stable and high electrocatalytic activities for OER in acidic solutions, showing an overpotential at a current density of 10 mA cm –2 and a Tafel slope as low as of 265 mV and 82 mV dec –1, respectively. As far as we are aware, these results represent the best OER performance for metal‐free electrocatalysts, even comparable to those of RuO2 and IrO2 . We have further revealed the catalytic mechanism, which involves one electron lose from the COOH‐MWNTs catalyst at the beginning of the OER process to trigger H2 O molecule oxidation by forming peralcohol, followed by the recapture of one electron from water molecule to oxidize water and to recover the initial state for the COOH‐MWNTs catalyst. The unravel of this new OER mechanism is important as it provides new insights into the crucial role of organic functional groups in electrocatalytic processes. Also, the mechanistic understanding can be used to guide the design and development of novel metal‐free catalysts for acidic OER electrocatalysis and beyond. Abstract : A catalytic mechanism was revealed, which involves one electron lose from the COOH‐MWNTs catalyst at the beginning of the OER process to trigger H2 O molecule oxidation by forming peralcohol, followed by the recapture of one electron from water molecule to oxidize water and to recover the initial state for the COOH‐MWNTs catalyst. carbon nanotubes, carboxylation defect, metal‐free, acidic oxygen evolution, catalytic mechanism.